Nomenclator botanicus for the neotropical genus Miconia (Melastomataceae: Miconieae) - Goldenberg, Renato; Almeda, Frank; Caddah, Mayara K.; Martins, Angela B.; Meirelles, Julia; Michelangeli, Fabian A.; Weiss, Markus (Phytotaxa, 2013)
Miconia has 1057 species and is the largest genus of woody flowering plants with a distribution restricted to tropical America. These species occur from Mexico (79 spp) to Argentina (10) and Uruguay (1), and attain highest richness in Colombia (338 spp), Peru (302), Brazil (274), Ecuador (254) and Venezuela (212). More than half of the species belong to only three sections (Miconia with 245, Cremanium with 223, and Amblyarrhena with 212). The other sections are Chaenopleura (86 spp), Glossocentrum (82), Tamonea (71), Octomeris (59), Jucunda (23), Laceraria (19), Chaenanthera (17), Hartigia (7), and Adenodesma (6), while seven species have not been assigned to any section. In this nomenclator we attempt to enumerate all currently accepted species of Miconia with place of publication, information on types, synonymy, sectional placement, and distributional notes organized by country.